Waterproof flame-retardant polyvinyl chloride modified particle and preparation method thereof
By using fusible polytetrafluoroethylene to wrap modified magnesium hydroxide in polyvinyl chloride and blending with expanded graphite and modified nanosilica, waterproof and flame-retardant polyvinyl chloride modified particles were prepared, solving the problem of degradation of water resistance and mechanical properties caused by inorganic flame retardants, and achieving efficient waterproofing and flame-retardant effects of polyvinyl chloride materials.
Patent Information
- Application Number
- CN202510288991.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing inorganic flame retardant used in the flame retardant modification of polyvinyl chloride has problems such as decreasing water resistance, degraded mechanical properties and limited flame retardant effect.
Fluoriable polytetrafluoroethylene wrapped modified magnesium hydroxide as a modified flame retardant and blended with expanded graphite and modified nanosilicon dioxide to prepare waterproof flame retardant polyvinyl chloride modified particles.
The waterproofness and flame retardancy of polyvinyl chloride materials are improved, and the mechanical properties and waterproof properties of inorganic flame retardants are solved. The modified particles obtained have excellent mechanical properties, hydrophobicity, self-cleaning properties, flame retardancy and other properties.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to waterproof and flame-retardant polyvinyl chloride modified particles and a preparation method thereof. Background Art
[0002] Generally, polyvinyl chloride is obtained through the polymerization reaction of vinyl chloride monomer. As an important thermoplastic, it has excellent mechanical strength, thermal stability, flame retardancy and insulation properties, and its production cost is low, so it has attracted much attention. According to statistics, the current output of PVC products has accounted for about 30% of the total output of thermoplastics. The chlorine content of polyvinyl chloride (PVC) is higher than that of other organic polymers, reaching 56.7% of the mass, which makes it have higher fire resistance and combustion resistance than most organic polymers. However, PVC products usually need to add a large amount of plasticizers during processing to improve their performance. Due to the addition of a large amount of plasticizers, the flame retardant performance is greatly reduced, and a large amount of smoke is generated during combustion, releasing toxic gases, which has great safety hazards. In a fire, smoke is the main factor threatening life safety, which will seriously delay people's escape and property rescue opportunities. Therefore, in order to make PVC composite materials have good flame retardancy and smoke suppression properties, flame retardants and smoke suppressants must be added.
[0003] At present, the flame retardant properties of materials can be improved by chemical or physical modification methods. Among them, doping a proper amount of inorganic flame retardants in polymers has the advantages of strong operability, simple equipment requirements, and easy industrial production, so it has attracted widespread attention. Magnesium hydroxide (MH), as a typical representative of magnesium-based flame retardants, can not only improve the mechanical properties of materials, but also improve the thermal stability of materials. It is widely used in the modification of polymer flame retardant properties. However, the main disadvantage of MH is that in order to achieve the ideal flame retardant effect, it is necessary to add more than 50% of the weight of PVC, but MH has a higher surface energy, while the surface energy of the PVC matrix is lower. This energy difference makes the compatibility between MH and the PVC matrix poor, thereby reducing the mechanical properties of PVC composites. In addition, the surface of MH particles is rich in hydroxyl groups (-OH), which are easy to adsorb water molecules in the environment through hydrogen bonds. If the MH particles are unevenly dispersed, micropores are easily formed at the interface between the agglomerate and the matrix, which becomes a water permeation channel, thereby reducing the waterproof performance of the PVC composite material. It is very difficult to maintain good mechanical properties after MH is filled into PVC while improving the waterproof and flame retardant properties of PVC composites. Therefore, existing polyvinyl chloride flame-retardant composite materials have defects such as low waterproofness, reduced mechanical properties and limited flame-retardant effect, which greatly limits the use of this technology. Summary of the invention
[0004] The purpose of the present invention is to provide a waterproof and flame-retardant polyvinyl chloride modified particle and a preparation method thereof, so as to solve the following technical problems: The existing inorganic flame retardants used for flame retardant modification of polyvinyl chloride have the problems of reduced waterproofness, reduced mechanical properties and limited flame retardant effect.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A waterproof and flame-retardant polyvinyl chloride modified particle comprises at least the following raw materials in parts by weight: 100 parts of polyvinyl chloride, 5-10 parts of maleic anhydride grafted polyvinyl chloride, 20-30 parts of modified flame retardant, 5-15 parts of expanded graphite, 2-5 parts of modified nano-silicon dioxide, 2-5 parts of diisononyl phthalate, 0.1-0.5 parts of antioxidant, 1-2 parts of lubricant, 3-5 parts of heat stabilizer; Wherein, the modified flame retardant is modified magnesium hydroxide particles wrapped by fusible polytetrafluoroethylene.
[0006] As a further solution of the present invention: the preparation method of the modified flame retardant comprises the following steps: Add concentrated ammonia water to a magnesium salt solution, then add polyethylene glycol 2000, perform a hydrothermal reaction, wash and dry to obtain nano magnesium hydroxide; Adding the hydrolyzate of γ-methacryloxypropyltrimethoxysilane to the dispersion of nano magnesium hydroxide, washing and drying after reaction, to obtain modified magnesium hydroxide; The modified magnesium hydroxide is added into a fusible polytetrafluoroethylene solution, the solvent is evaporated and sintered to obtain a modified flame retardant.
[0007] As a further solution of the present invention: the concentrated ammonia water is a 25-30wt% ammonia water solution, and the concentration of magnesium ions in the magnesium salt solution is 0.5-1 mol / L.
[0008] As a further solution of the present invention: the mass of the γ-methacryloxypropyltrimethoxysilane is 4-5% of the mass of the nano-magnesium hydroxide, and the mass ratio of the fusible polytetrafluoroethylene to the modified magnesium hydroxide is 7:2-3.
[0009] As a further solution of the present invention: the preparation method of the modified nano-silicon dioxide comprises the following steps: Disperse nano-silicon dioxide in ethanol to obtain nano-silicon dioxide dispersion: Trimethylchlorosilane is added into the nano-silicon dioxide dispersion, reacted, washed and dried to obtain modified nano-silicon dioxide.
[0010] As a further solution of the present invention: the mass ratio of the trimethylchlorosilane to the nano-silicon dioxide is 1-2:10.
[0011] As a further solution of the present invention: the antioxidant includes at least one of antioxidant 1010 and antioxidant 168 or a mixture of the two.
[0012] As a further embodiment of the present invention: the lubricant includes at least any one of stearic acid and its esters, stearates, polyethylene wax, oxidized polyethylene wax, paraffin, stearic acid amide, and oleic acid amide, or a mixture of more than one of them.
[0013] As a further solution of the present invention: the heat stabilizer includes at least one of a lead-free calcium-zinc composite stabilizer and a rare earth stabilizer, or a mixture of the two.
[0014] A method for preparing the waterproof and flame-retardant polyvinyl chloride modified particles as described in any one of the above, comprising at least the following steps: Prepare raw materials according to the components by mass, add all the raw materials into a mixer and mix them evenly to obtain a mixture; The mixed material is added into a twin-screw extruder, extruded at 200-220° C., granulated and dried to obtain waterproof and flame-retardant polyvinyl chloride modified particles.
[0015] Beneficial effects of the present invention: The invention uses polyvinyl chloride as a substrate, adds modified magnesium hydroxide wrapped by fusible polytetrafluoroethylene as a modified flame retardant, expandable graphite and modified nano silicon dioxide for blending, and prepares waterproof and flame-retardant polyvinyl chloride modified particles, improves the waterproofness and flame retardancy of polyvinyl chloride composite materials, solves the problem of decreased mechanical properties and waterproof properties caused by adding inorganic flame retardants in polyethylene substrates, and the waterproof and flame-retardant polyvinyl chloride modified particles prepared by the method of the invention have excellent mechanical properties, hydrophobicity, self-cleaning property, flame retardancy, mildew resistance, aging resistance, low water vapor permeability, compatibility, oxidation resistance and the like, and can be widely used in the fields of building waterproofing coiled materials, cable sheaths, outdoor equipment, daily necessities, various pipes and the like.
[0016] In the present invention, maleic anhydride grafted polyvinyl chloride is added as a compatibilizer, the compatibility of the modified flame retardant wrapped by fusible polytetrafluoroethylene and the matrix is improved, the processing difficulty is reduced, the dispersibility and compatibility of the modified flame retardant in the matrix are improved, and the fusible polytetrafluoroethylene has excellent high temperature resistance, chemical corrosion resistance and low friction coefficient, giving the material chemical corrosion resistance and hydrophobic properties. In the present invention, expanded graphite is also added for synergistic flame retardancy, the lamellar structure of the expanded graphite blocks water molecules, and forms a synergistic flame retardant-waterproof network with magnesium hydroxide, reducing the amount of modified flame retardant used, avoiding the decline of mechanical properties of polyvinyl chloride, and further improving the flame retardancy of polyvinyl chloride materials. When the modified flame retardant provided by the present invention burns in the substrate, the fusible tetrafluoroethylene can prevent the polyvinyl chloride from melting and dripping. After the fusible polytetrafluoroethylene melts at 290-312°C to expose the modified magnesium hydroxide, the modified magnesium hydroxide changes from the initial temperature of 340°C at the beginning of decomposition to 490°C when it is completely decomposed. In this process, the crystal water obtained by hydrolysis can absorb heat and become water vapor, thereby reducing the concentration of gas phase combustibles, while inhibiting the temperature increase of the combustion products and preventing continued combustion. At the same time, the decomposition product MgO protective film and the carbon layer generated by the thermal expansion of the expanded graphite cover the surface of the substrate, forming a protective layer that isolates flames and heat, preventing the combustion products from continuing to contact with oxygen, and hindering the heat transfer capacity, thereby achieving a flame retardant and smoke suppression effect.
[0017] The modified flame retardant prepared by the invention utilizes the methoxy groups on gamma-methacryloxypropyltrimethoxysilane to hydrolyze to generate silanol groups, releases the hydrolysis product methanol, and simultaneously, a large amount of free hydroxide ions on the surface of nano magnesium hydroxide particles undergo dehydration condensation with the silanol groups obtained by hydrolyzing the gamma-methacryloxypropyltrimethoxysilane, thereby linking the two through chemical bonds, thereby achieving the modification of the surface of the nano magnesium hydroxide particles by the gamma-methacryloxypropyltrimethoxysilane, increasing the hydrophobicity of the surface of the nano magnesium hydroxide, effectively improving the activity of the magnesium hydroxide, thereby improving the interface adhesion and compatibility problems between the magnesium hydroxide and the fusible polytetrafluoroethylene, making the fusible polytetrafluoroethylene wrap around the surface of the magnesium hydroxide, improving the flame retardant and smoke suppression performance, and avoiding the reduction of the mechanical properties and waterproofness of the polyvinyl chloride modified particles. The present invention also adds modified nano-silica. The added modified nano-silica is converted into silanol by hydrolysis of trimethylchlorosilane, reacts with hydroxyl groups on the surface of the nano-silica, and grafts the silanol to the surface of the nano-silica through hydrogen bond interaction, forming steric hindrance between the nano-silica particles, preventing the agglomeration of the particles, filling the gaps between the modified flame retardant particles, reducing the penetration path of water molecules, reducing the water absorption rate of the overall system, and further improving the waterproofness of the material. DETAILED DESCRIPTION
[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] Example 1 The preparation method of the modified flame retardant comprises the following steps: A magnesium salt solution with a magnesium ion concentration of 0.5 mol / L was prepared, concentrated ammonia water was added dropwise to adjust the pH to 10, polyethylene glycol 2000 was added and stirred for 30 minutes, and then reacted at 120°C for 8 hours. After washing, it was placed in a vacuum drying oven at 80°C for 12 hours to obtain nano magnesium hydroxide, wherein the addition amount of polyethylene glycol 2000 was 4% of the mass of the magnesium salt; γ-methacryloxypropyltrimethoxysilane and solvent (anhydrous ethanol: deionized water 9:1) are prepared into KH-570 hydrolyzate, and the pH is adjusted to 3. The KH-570 hydrolyzate is added to the dispersion of nano magnesium hydroxide prepared above, and magnetic stirring is maintained. The reaction is carried out at 60° C. for 1 hour, and modified magnesium hydroxide is obtained after washing and drying, wherein the addition amount of γ-methacryloxypropyltrimethoxysilane is 4% of the mass of nano magnesium hydroxide; Fusible polytetrafluoroethylene was dissolved in perfluoropolyether oil to prepare a 10wt% solution, and the modified magnesium hydroxide prepared above was added and ultrasonically dispersed for 1 hour. After spray drying (inlet temperature 250°C, outlet temperature 120°C), hot pressing was performed at 300°C and 10MPa for 5min to obtain a modified flame retardant, wherein the mass ratio of fusible polytetrafluoroethylene to modified magnesium hydroxide was 7:3.
[0020] Example 2 The preparation method of the modified flame retardant comprises the following steps: A magnesium salt solution with a magnesium ion concentration of 0.5 mol / L was prepared, concentrated ammonia water was added dropwise to adjust the pH to 10, polyethylene glycol 2000 was added and stirred for 30 minutes, and then reacted at 120°C for 8 hours. After washing, it was placed in a vacuum drying oven at 80°C for 12 hours to obtain nano magnesium hydroxide, wherein the addition amount of polyethylene glycol 2000 was 4% of the mass of the magnesium salt; γ-methacryloxypropyltrimethoxysilane and solvent (anhydrous ethanol: deionized water 9:1) are prepared into KH-570 hydrolyzate, and the pH is adjusted to 3. The KH-570 hydrolyzate is added to the dispersion of the nano magnesium hydroxide prepared above, and magnetic stirring is maintained. The reaction is carried out at 60° C. for 1 hour, and modified magnesium hydroxide is obtained after washing and drying, wherein the addition amount of γ-methacryloxypropyltrimethoxysilane is 5% of the mass of the nano magnesium hydroxide; Fusible polytetrafluoroethylene was dissolved in perfluoropolyether oil to prepare a 10wt% solution, and the modified magnesium hydroxide prepared above was added and ultrasonically dispersed for 1h. After spray drying (inlet temperature 250°C, outlet temperature 120°C), hot pressing was performed at 300°C and 10MPa for 5min to obtain a modified flame retardant, wherein the mass ratio of fusible polytetrafluoroethylene to modified magnesium hydroxide was 7:2.
[0021] Example 3 The preparation method of modified nano-silicon dioxide comprises the following steps: 5 g of nano-silicon dioxide particles were added to 200 mL of anhydrous ethanol and ultrasonically treated for 15 min to obtain a nano-silicon dioxide dispersion; 1 g of trimethylchlorosilane was added to the nano-silica dispersion obtained above, reacted at 50° C. for 16 h, centrifuged at 10,000 r / min for 10 min, washed twice with anhydrous ethanol, dried at a constant temperature of 60° C. for 24 h, and fully ground to obtain modified nano-silica.
[0022] Example 4 The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 30 parts by mass of the modified flame retardant prepared in Example 1, 8 parts by mass of maleic anhydride grafted polyvinyl chloride, 10 parts by mass of expanded graphite, 3 parts by mass of the modified silica prepared in Example 3, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed, and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0023] Example 5 The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 30 parts by mass of the modified flame retardant prepared in Example 2, 8 parts by mass of maleic anhydride grafted polyvinyl chloride, 10 parts by mass of expanded graphite, 3 parts by mass of the modified silica prepared in Example 3, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed, and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0024] Example 6 The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 25 parts by mass of the modified flame retardant prepared in Example 1, 5 parts by mass of maleic anhydride grafted polyvinyl chloride, 8 parts by mass of expanded graphite, 3 parts by mass of the modified silica prepared in Example 3, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed, and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0025] Example 7 The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 25 parts by mass of the modified flame retardant prepared in Example 2, 5 parts by mass of maleic anhydride grafted polyvinyl chloride, 8 parts by mass of expanded graphite, 3 parts by mass of the modified silica prepared in Example 3, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed, and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0026] Comparative Example 1 The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 30 parts by mass of the modified magnesium hydroxide prepared in Example 1, 8 parts by mass of maleic anhydride grafted polyvinyl chloride, 10 parts by mass of expanded graphite, 3 parts by mass of the modified silicon dioxide prepared in Example 3, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed, and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0027] Comparative Example 2 The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 30 parts by mass of the modified flame retardant prepared in Example 1, 8 parts by mass of maleic anhydride grafted polyvinyl chloride, 10 parts by mass of expanded graphite, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0028] Comparative Example 3 The preparation method of the modified flame retardant comprises the following steps: A magnesium salt solution with a magnesium ion concentration of 0.5 mol / L was prepared, concentrated ammonia water was added dropwise to adjust the pH to 10, polyethylene glycol 2000 was added and stirred for 30 minutes, and then reacted at 120°C for 8 hours. After washing, it was placed in a vacuum drying oven at 80°C for 12 hours to obtain nano magnesium hydroxide, wherein the addition amount of polyethylene glycol 2000 was 4% of the mass of the magnesium salt; γ-methacryloxypropyltrimethoxysilane and solvent (anhydrous ethanol: deionized water 9:1) are prepared into KH-570 hydrolyzate, and the pH is adjusted to 3. The KH-570 hydrolyzate is added to the dispersion of nano magnesium hydroxide prepared above, and magnetic stirring is maintained. The reaction is carried out at 60° C. for 1 hour, and modified magnesium hydroxide is obtained after washing and drying, wherein the addition amount of γ-methacryloxypropyltrimethoxysilane is 4% of the mass of nano magnesium hydroxide; Fusible polytetrafluoroethylene and modified magnesium hydroxide are blended in a mass ratio of 7:3 to obtain a modified flame retardant.
[0029] The preparation method of waterproof and flame-retardant polyvinyl chloride modified particles comprises the following steps: 100 parts by mass of polyvinyl chloride (SG-3, purchased from Shaanxi Beiyuan Chemical Group Co., Ltd.), 30 parts by mass of the modified flame retardant prepared in Comparative Example 3, 8 parts by mass of maleic anhydride grafted polyvinyl chloride, 10 parts by mass of expanded graphite, 3 parts by mass of the modified silica prepared in Example 3, 2 parts by mass of diisononyl phthalate, 0.2 parts by mass of antioxidant 168, 1 part by mass of polyethylene wax and 3 parts by mass of calcium zinc composite stabilizer were mixed, and stirred at high speed for 5 minutes to obtain a mixture; The mixed material obtained above is added into a twin-screw extruder, and after extrusion, granulation and drying at 200-220° C., waterproof and flame-retardant polyvinyl chloride modified particles are obtained.
[0030] Performance Testing Limiting oxygen index (LOI) test: According to GB / T 2406.2-2009 standard, use M606B oxygen index tester (LOI, M606B, China), test sample size (100.0mm×10.0mm×4.0mm), under N2 and O2 mixed gas conditions, record time and observe the combustion of the test sample at the same time, test a group of samples in different O2 concentrations, after multiple measurements (5-10 times), record the lowest oxygen concentration when the sample just maintains stable combustion, and take the LOI value; the test results are shown in Table 1 Vertical combustion (UL-94) test: test sample UL-94 grade, sample size is 130.0mm×10.0mm×4.0mm, test standard is GB / T 2408-2008; test results are shown in Table 1 Mechanical properties test: The electronic universal material testing machine (Instron-6800, USA) was used to conduct mechanical properties tests on the test samples according to GB / T1040.1-2006 standard. The tensile rate was 50 mm / min. Five samples were selected in each group to test their tensile strength and elongation at break, and the average values were taken. The test results are shown in Table 1. Water absorption test: According to GB / T 1034-2008, the water resistance of the sample was tested. The sample was immersed in (23±2)℃ water for 3 days and then taken out. After wiping off the surface moisture, the sample was weighed m1 and the water absorption of the sample was calculated. The test results are shown in Table 1. Water resistance coefficient: Soak the sample in water until the liquid level is 5 cm above the specimen. Take it out after 7 days of soaking, wipe off the surface moisture, test its compressive strength RT, and calculate the water resistance coefficient k of the specimen: k=R T / R0In the formula, k-water resistance coefficient; R0-initial compressive strength of the sample, kPa; R T - Compressive strength of the sample after 7 days of water immersion, kPa; the test results are shown in Table 1; Table 1: Statistical table of performance test data of test pieces of Examples 4-7 and Comparative Examples 1-3 Vertical burning level Limiting oxygen index (%) Tensile strength (MPa) Elongation at break (%) Water resistance coefficient Water absorption (wt%) Example 4 V0 36.7 16.9 280 0.93 0.2 Example 5 V0 35.2 16.2 285 0.88 0.2 Example 6 V0 34.8 16.8 280 0.91 0.2 Example 7 V0 34.2 16.2 276 0.92 0.2 Comparative Example 1 V0 31.2 15.2 268 0.59 0.3 Comparative Example 2 V0 34.0 13.5 245 0.79 0.5 Comparative Example 3 V1 28.2 8.2 215 0.43 0.8 As can be seen from Table 1, the waterproof and flame-retardant polyvinyl chloride modified particles prepared by the present invention have good flame retardancy and water resistance, and the mechanical properties are also improved. In Comparative Example 1, the modified magnesium hydroxide added replaces the prepared modified flame retardant, and the flame retardancy and water resistance of the obtained polyvinyl chloride modified particles are reduced. In Comparative Example 2, no modified silicon dioxide particles are added, and the water resistance and mechanical properties of the obtained polyvinyl chloride modified particles are reduced. In Comparative Example 3, the fusible polytetrafluoroethylene is not wrapped on the surface of the modified magnesium hydroxide, and the flame retardancy and water resistance of the obtained polyvinyl chloride modified particles are reduced, and the mechanical properties of the polyvinyl chloride material are greatly reduced. It shows that the present invention can improve the flame retardancy and water resistance of polyvinyl chloride materials by adding modified flame retardants and modified silicon dioxide, and will not reduce the mechanical properties of the composite material. In addition, in the present invention, the modified magnesium hydroxide is wrapped with fusible polytetrafluoroethylene to prepare a modified flame retardant and added to the matrix, which has better flame retardancy and water resistance than adding the fusible polytetrafluoroethylene and the modified magnesium hydroxide separately to the matrix, and avoids a significant decrease in mechanical properties.
[0031] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A waterproof and flame-retardant polyvinyl chloride modified particle, characterized in that: At least the following raw materials are included: 100 parts of polyvinyl chloride, 5-10 parts of maleic anhydride grafted polyvinyl chloride, 20-30 parts of modified flame retardant, 5-15 parts of expanded graphite, 2-5 parts of modified nano-silicon dioxide, 2-5 parts of diisononyl phthalate, 0.1-0.5 parts of antioxidant, 1-2 parts of lubricant, 3-5 parts of heat stabilizer; Wherein, the modified flame retardant is modified magnesium hydroxide particles wrapped by fusible polytetrafluoroethylene.
2. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 1, characterized in that: The preparation method of the modified flame retardant comprises the following steps: Add concentrated ammonia water to a magnesium salt solution, then add polyethylene glycol 2000, perform a hydrothermal reaction, wash and dry to obtain nano magnesium hydroxide; Adding the hydrolyzate of γ-methacryloxypropyltrimethoxysilane to the dispersion of nano magnesium hydroxide, washing and drying after reaction, to obtain modified magnesium hydroxide; The modified magnesium hydroxide is added into a fusible polytetrafluoroethylene solution, the solvent is evaporated and sintered to obtain a modified flame retardant.
3. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 2, characterized in that: The concentrated ammonia solution is 25-30wt% ammonia solution, and the concentration of magnesium ions in the magnesium salt solution is 0.5-1 mol / L.
4. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 2, characterized in that: The mass of the γ-methacryloxypropyltrimethoxysilane is 4-5% of the mass of the nano magnesium hydroxide, and the mass ratio of the fusible polytetrafluoroethylene to the modified magnesium hydroxide is 7:2-3.
5. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 1, characterized in that: The preparation method of the modified nano-silicon dioxide comprises the following steps: Disperse nano-silicon dioxide in ethanol to obtain nano-silicon dioxide dispersion: Trimethylchlorosilane is added into the nano-silicon dioxide dispersion, reacted, washed and dried to obtain modified nano-silicon dioxide.
6. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 5, characterized in that: The mass ratio of the trimethylchlorosilane to the nano-silicon dioxide is 1-2:
10.
7. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 1, characterized in that: The antioxidant includes at least one of the antioxidant 1010 and the antioxidant 168 or a mixture of the two.
8. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 1, characterized in that: The lubricant includes at least one of stearic acid and its esters, stearates, polyethylene wax, oxidized polyethylene wax, paraffin, stearic acid amide, and oleic acid amide, or a mixture of more than one of them.
9. The waterproof and flame-retardant polyvinyl chloride modified particles according to claim 1, characterized in that: The heat stabilizer includes at least one of a lead-free calcium-zinc composite stabilizer and a rare earth stabilizer or a mixture of the two.
10. A method for preparing the waterproof and flame-retardant polyvinyl chloride modified particles according to any one of claims 1 to 9, characterized in that: At least the following steps are included: Prepare raw materials according to the components by mass, add all the raw materials into a mixer and mix them evenly to obtain a mixture; The mixed material is added into a twin-screw extruder, extruded at 200-220° C., granulated and dried to obtain waterproof and flame-retardant polyvinyl chloride modified particles.
Citation Information
Patent Citations
High-flame-retardant high-thermal-conductive PVC (polyvinyl chloride) compound cable material and preparation method thereof
CN109096656A
Polyvinyl chloride cable material and preparation method thereof
CN118667267A
Vinyl chloride resin composition for cable sheath material, and highly flame-retardant cable
JP2016044294A